University Knowledge Spillover, Intellectual Property Protection, and Innovation Performance: Evidence from Chinese High-Tech Enterprises - Xinran Yang; Dashuai Huang; Bingfei Liu (SAGE Open)
This study investigates how university knowledge spillovers and intellectual property (IP) protection jointly influence innovation performance in high-tech firms. Analysing an unbalanced panel dataset of China’s A-share listed companies (475 firms; 3,339 observations) and higher education institutions in Guangdong Province (2011–2020), we employ a Cobb-Douglas production function measured through total factor productivity. Empirical results reveal substantial heterogeneity in innovation levels across technology firms. Critically, university knowledge spillovers exhibit a significant positive effect on innovation performance, while IP protection exerts a negative moderating effect that attenuates spillover efficacy. These findings extend theoretical frameworks on knowledge spillovers and corporate innovation, refine understanding of IP governance trade-offs, and provide actionable evidence for corporate strategy and science policy design.